Special silk screen membrane for bone repair and preparation method thereof
The bone repair special silk retina prepared by electrostatic spinning technology, combined with anti -inflammatory drugs, nano -inorganic calcium salts and biodeeeable polymers to solve the problem of rapid degradation of magnesium alloys in the body, realizing effective anti -inflammatory and bone repair restoration Effect.
Patent Information
- Application Number
- CN202411514068.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The rapid degradation of existing magnesium alloys in the body causes the material to corrode before the body recovers, reducing the mechanical properties and stability of the material, and may cause harm to human bones and tissues, limiting its clinical application.
Use electrostatic spinning technology to prepare bone repair special silk oments, add anti -inflammatory drugs, nano -inorganic calcium salts and biochemical polymers, improve the ability to add anti -inflammatory drugs by plasma treatment, and buffer the pH value change during degradation process. , Control the corrosion speed of magnesium alloy.
Effectively alleviate the sterile inflammation generated by the degradation of magnesium alloy, extend the degradation time of magnesium alloy materials, improves the mechanical properties and stability of bone repair materials, and enhances support for bone repair.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a silk screen membrane specially used for bone repair and a preparation method thereof. Background Art
[0002] Guided bone regeneration (GBR) is a treatment method for bone rehabilitation in the clinical field. Guided bone regeneration uses a barrier membrane to guide the ingrowth of fibrous tissue to guide bone reconstruction and achieve new bone growth. Bioresorbable membranes can avoid secondary surgery and reduce tissue morbidity and loss of new bone. Biodegradable polymers such as polylactic acid (PLA) or polylactic-co-glycolic acid (PLGA) have been widely studied as membrane materials.
[0003] Magnesium alloys are a hot topic in the field of biomedical biodegradable metal implant materials because of their good absorbability, biocompatibility, complete degradability and low price. However, the standard electrode potential of magnesium is very low, especially the Cl in body fluids. - It will accelerate the corrosion of magnesium alloys. The faster degradation rate causes serious corrosion of the implant material before the body recovers, reducing the mechanical properties and stability of the material. Moreover, the excessively fast degradation rate will increase the local pH value of the body fluid near the implant, causing harm to human bones and group growth, thus seriously restricting the clinical application of magnesium alloys.
[0004] Chinese patent (CN201310586143.0, publication date: March 5, 2014) discloses that a new biodegradable guided bone regeneration membrane is prepared by electrospinning a mixture of hydroxyapatite grafted polylactic acid (HA-g-PLLA) nanoparticles and poly (L-lactide co-glycolide) (PLGA). The membrane has good mechanical properties, and the tensile properties of the membrane are the best when the content of hydroxyapatite grafted PLLA is 5%, and the cell adhesion performance is also better than that of pure PLGA fiber membrane. However, this technical solution only provides a guided bone regeneration membrane, and the use of the membrane with bone nails, bone plates and other materials for bone repair is still unclear.
[0005] Chinese patent (201910336888.9, announcement date: June 28, 2019) discloses a multifunctional electrospun fiber dressing and its preparation method, which is obtained by spinning a polymer material grafted with antioxidant groups and / or antibacterial groups into fibers by an electrospinning method and then cross-linking, wherein the polymer material has the function of stimulating macrophage transformation. Antioxidant groups include fluorine-containing groups, phenylboronic acid, thioether, oxalate, selenoether, alkyl diselenide or thioketal, and antibacterial groups include quaternary ammonium salts, quaternary phosphonium salts, organic tin, halogenated amines, amino acids, and pyridinium salts. The dressing is an external material, which does not require high degradation performance of the material and does not involve requirements related to bone repair. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the technical solution provided by the present invention is:
[0007] A silk screen membrane specially used for bone repair comprises anti-inflammatory drugs, nano inorganic calcium salts and biodegradable polymers.
[0008] Preferably, the bone repair silk screen membrane may also include potassium citrate and sodium bicarbonate to buffer pH changes that occur during the degradation of materials such as magnesium alloy bone screws and plates and polylactic acid.
[0009] Preferably, the anti-inflammatory drug is one or more combinations of nimesulide, curcumin, bleomycin, cyclophosphamide, celecoxib, doxorubicin hydrochloride, doxorubicin, etoricoxib, and meloxicam.
[0010] Preferably, the nano inorganic calcium salt is at least one of nano tricalcium phosphate, nano hydroxyapatite and nano calcium silicate.
[0011] Preferably, the biodegradable polymer is polylactic acid.
[0012] Preferably, the mass ratio of the nano inorganic calcium salt to the biodegradable polymer is 1:10-100.
[0013] The method for preparing the special silk screen membrane for bone repair comprises the following steps:
[0014] Step 1: dissolving 10-100 parts of dried biodegradable polymer in a solvent, adding 1 part of nano inorganic calcium salt, 0.5-2 parts of grafted polymer, and 0.1-0.3 parts of catalyst, stirring and reacting at 50-80° C. for 1-3 hours to obtain a spinning solution;
[0015] The solvent is a mixture of any two of dichloromethane, chloroform and N,N-dimethylformamide; the grafted polymer is any one of chitosan, dextran and dopamine; and the catalyst is any one of stannous chloride and stannous lactate.
[0016] Step 2: Spinning the spinning solution obtained in step 1 in an electrospinning machine, the spinning voltage is 12-25 kV, a No. 20 needle with an inner diameter of 0.6 mm is used, the distance between the spinneret and the receiving screen is 20-25 cm, the receiving screen is a stationary flat plate covered with aluminum foil, the spinning solution flow rate is 2-3 mm / min, the spinning temperature is 20-30° C., and an electrospinning membrane is obtained;
[0017] Step 3: Place the electrospun membrane in 60% ethanol, clean it with an ultrasonic cleaner for 10 minutes, take it out and rinse it with deionized water, and dry it in an oven at 30-40°C for later use;
[0018] Step 4: placing the electrospun membrane cleaned and dried in step 3 between the two electrodes of a normal pressure plasma treatment device, and performing plasma treatment for 90 to 180 seconds in an argon atmosphere at a discharge voltage of 200V;
[0019] Step 5: prepare the anti-inflammatory drug into a saturated solution, immerse the electrospun membrane treated by plasma in step 4 in the saturated solution of the anti-inflammatory drug for 30 minutes, take it out and dry it to obtain a silk screen membrane for bone repair.
[0020] Compared with the prior art, the present invention has the following advantages: 1. The bone repair-specific silk screen membrane provided by the present invention uses a grafted polymer, a catalyst, etc. to graft nano inorganic calcium salts onto polylactic acid molecular chains, so that the silk screen membrane continuously releases bone repair factors during the degradation process, which is more conducive to bone repair; 2. The electrostatic spinning membrane is treated with plasma, and the treated electrostatic spinning membrane has a better adhesion ability to anti-inflammatory drugs. The membrane is used in combination with materials such as magnesium alloy bone nails and bone plates to effectively alleviate aseptic inflammation caused by magnesium alloy degradation; 3. The present invention also adds potassium citrate and sodium bicarbonate to the silk screen membrane to buffer the pH changes during the degradation of magnesium alloy bone nails, bone plates and polylactic acid, thereby prolonging the onset time of magnesium alloy bone nails and bone plates; 4. The number of silk screen membrane layers is calculated according to the amount of magnesium alloy bone nails and bone plates used, and the corrosion rate of magnesium alloy is controlled by 1-5 layers of silk screen membrane, so that the magnesium alloy material can give full play to its efficacy. DETAILED DESCRIPTION
[0021] Next, embodiments of the present invention will be described.
[0022] Embodiment 1:
[0023] Dichloromethane and N,N-dimethylformamide were prepared as solvents in a ratio of 1:1, 10 parts of dried polylactic acid were dissolved in the above solvent, 1 part of nanohydroxyapatite, 2 parts of dextran as grafted polymer, and 0.3 parts of stannous lactate as catalyst were added, and the spinning solution was obtained by stirring and reacting for 2 hours at 80°C. The above spinning solution was spun in an electrospinning machine, the spinning voltage was 14kV, a No. 20 needle with an inner diameter of 0.6mm was used, the distance between the spinneret and the receiving screen was 25cm, the receiving screen was a stationary flat plate covered with aluminum foil, the spinning solution flow rate was 2mm / min, the spinning temperature was 25°C, and an electrospinning membrane was obtained. The electrospinning membrane was placed in 60% ethanol, cleaned with an ultrasonic cleaner for 10 minutes, taken out and washed with deionized water, and dried in an oven at 40°C. The electrospun membrane after cleaning and drying was placed between the two electrodes of the atmospheric pressure plasma treatment equipment, and plasma treatment was performed for 100 seconds in an argon atmosphere at a discharge voltage of 200 V. Doxorubicin hydrochloride was prepared into a saturated solution, and the electrospun membrane after the plasma treatment was immersed in the saturated solution of the anti-inflammatory drug for 30 minutes, and then taken out and dried to obtain the bone repair special silk screen membrane M1.
[0024] Embodiment 2:
[0025] Dichloromethane and N,N-dimethylformamide were prepared as solvents in a ratio of 1:1, 10 parts of dried polylactic acid were dissolved in the above solvent, 1 part of nanohydroxyapatite, 2 parts of dextran as grafted polymer, 0.3 parts of stannous lactate as catalyst, 0.6 parts of potassium citrate and 0.75 parts of sodium bicarbonate were added, and the spinning solution was fully stirred and reacted at 80°C for 2h. The spinning solution was spun in an electrospinning machine, the spinning voltage was 14kV, a No. 20 needle with an inner diameter of 0.6mm was used, the distance between the spinneret and the receiving screen was 25cm, the receiving screen was a stationary flat plate covered with aluminum foil, the spinning solution flow rate was 2mm / min, the spinning temperature was 25°C, and an electrospinning membrane was obtained. The electrospinning membrane was placed in 60% ethanol, cleaned with an ultrasonic cleaner for 10min, taken out and washed with deionized water, and dried in an oven at 40°C. The electrospun membrane after cleaning and drying was placed between the two electrodes of the atmospheric pressure plasma treatment equipment, and plasma treatment was performed for 100 seconds in an argon atmosphere at a discharge voltage of 200 V. Doxorubicin hydrochloride was prepared into a saturated solution, and the electrospun membrane after the plasma treatment was immersed in the saturated solution of the anti-inflammatory drug for 30 minutes, and then taken out and dried to obtain the bone repair special silk screen membrane M2.
[0026] Embodiment 3:
[0027] Chloroform and N,N-dimethylformamide were prepared as solvents in a ratio of 1.2:1, 100 parts of dried polylactic acid were dissolved in the above solvent, 1 part of nano-tricalcium phosphate, 0.6 parts of chitosan as grafted polymer, and 0.1 parts of stannous chloride as catalyst were added, and the spinning solution was obtained by stirring and reacting for 3 hours at 55°C. The above spinning solution was spun in an electrospinning machine, the spinning voltage was 20kV, a No. 20 needle with an inner diameter of 0.6mm was used, the distance between the spinneret and the receiving screen was 20cm, the receiving screen was a stationary flat plate covered with aluminum foil, the spinning solution flow rate was 3mm / min, the spinning temperature was 20°C, and an electrospinning membrane was obtained. The electrospinning membrane was placed in 60% ethanol, cleaned with an ultrasonic cleaner for 10 minutes, taken out and washed with deionized water, and dried in an oven at 35°C. The electrospun membrane after cleaning and drying was placed between the two plates of the atmospheric pressure plasma treatment equipment, and plasma treatment was performed for 180 seconds in an argon atmosphere at a discharge voltage of 200 V. Etoricoxib was prepared into a saturated solution, and the electrospun membrane after the plasma treatment was immersed in the saturated solution of the anti-inflammatory drug for 30 minutes, and then taken out and dried to obtain the bone repair special silk screen membrane M3.
[0028] Embodiment 4:
[0029] Chloroform and N,N-dimethylformamide were prepared as solvents in a ratio of 1.2:1, 100 parts of dried polylactic acid were dissolved in the above solvent, 1 part of nano-tricalcium phosphate, 0.6 parts of chitosan as grafted polymer, 0.1 parts of stannous chloride as catalyst, 0.6 parts of potassium citrate and 0.75 parts of sodium bicarbonate were added, and the spinning solution was obtained by stirring and reacting for 3 hours at 55°C. The above spinning solution was spun in an electrospinning machine, the spinning voltage was 20kV, a No. 20 needle with an inner diameter of 0.6mm was used, the distance between the spinneret and the receiving screen was 20cm, the receiving screen was a stationary flat plate covered with aluminum foil, the spinning solution flow rate was 3mm / min, the spinning temperature was 20°C, and an electrospinning membrane was obtained. The electrospinning membrane was placed in 60% ethanol, cleaned with an ultrasonic cleaner for 10 minutes, taken out and washed with deionized water, and dried in an oven at 35°C. The electrospun membrane after cleaning and drying was placed between the two electrodes of the atmospheric pressure plasma treatment equipment, and plasma treatment was performed for 180 seconds in an argon atmosphere at a discharge voltage of 200 V. Etoricoxib was prepared into a saturated solution, and the electrospun membrane after the plasma treatment was immersed in the saturated solution of the anti-inflammatory drug for 30 minutes, and then taken out and dried to obtain the bone repair special silk screen membrane M4.
[0030] Antibacterial performance test:
[0031] A single colony of Staphylococcus aureus was picked and inoculated into 5 mL of LB liquid medium and cultured in a shaking incubator at 37 °C for 24 h to obtain a concentration of 1X109 CFUml bacterial suspension. Dilute the original bacteria to 1X10 with sterile phosphate buffered saline. 5 CFUmL, take 5 portions of bacterial dilution, 5 ml each, numbered J1-J5, weigh 40 mg of each of the bone repair special silk screen membranes M1-M4, add them to the bacterial dilutions numbered J1-J4, and the bacterial dilution numbered J5 is used as the control group. Incubate in a shaker at 250 r / min and 37°C for 12 hours, take 100 μL of bacterial suspension and evenly spread it on the agar plate for bacterial counting.
[0032] The results showed that in the J1-J4 dilutions with the addition of the bone repair-specific silk screen membranes M1-M4, the number of Staphylococcus aureus was significantly less than that in the control group J5, indicating that the anti-inflammatory drugs had good adhesion on the silk screen membranes and that the silk screen membranes had antibacterial effects.
[0033] Degradation performance test:
[0034] Take magnesium alloy substrate to make 15 flat specimens, 3 pieces in a group, numbered K1-K5, the surface of each specimen in group K1 is wrapped with three layers of bone repair special silk screen membrane M1, the surface of each specimen in group K2 is wrapped with three layers of bone repair special silk screen membrane M2, the surface of each specimen in group K3 is wrapped with three layers of bone repair special silk screen membrane M3, the surface of each specimen in group K4 is wrapped with three layers of bone repair special silk screen membrane M4, and the surface of the specimen in group K5 is not wrapped as a comparative example. The above five groups of specimens are immersed in artificial plasma according to the group, and the artificial plasma is replaced every 24 hours. The specimens are weighed every day, and the time for the specimens to degrade to 30% of the initial weight is recorded. The average time used for each group of 3 specimens is the degradation time.
[0035] The specific test data are shown in the following table:
[0036] Table 1 Test data table
[0037] K1 K2 K3 K4 K5 Degradation time 153d 177d 185d 203d 108d
[0038] It can be seen that the use of bone repair silk screen can significantly prolong the degradation time of magnesium alloy substrates, and as the content of nano inorganic calcium salt in the silk screen decreases, the degradation time of magnesium alloy substrates also prolongs. In addition, adding potassium citrate and sodium bicarbonate to the silk screen can also prolong the degradation time of magnesium alloy substrates.
[0039] Bone repair performance test:
[0040] Five flat specimens were made of magnesium alloy substrates, numbered L1-L5, and three layers of bone repair-specific silk screen membranes M1-M4 were included on the surface of specimens L1-L4, respectively, and L5 was used as the control group. Mouse embryonic osteoblasts were inoculated on the surface of L1-L5, and each specimen was immersed in simulated blood, and the simulated blood was replaced once a day during the immersion period. The absorbance value at a wavelength of 490nm was measured by an ELISA instrument on the 1st, 4th and 7th days, and the relative proliferation rate of the control group L5 was 100%. After conversion, the relative proliferation rate of each bone repair material L1-L4 was obtained, and the specific results are shown in Table 2 below. The results show that the higher the content of nano-inorganic calcium salt in the silk screen membrane, the more conducive it is to the growth of mouse embryonic osteoblasts.
[0041] Table 2 Relative cell proliferation rate %
[0042] Day 1 Day 4 Day 7 L1 137 156 148 L2 135 151 147 L3 116 135 132 L4 118 141 130 L5 100 100 100
[0043] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A special silk screen membrane for bone repair, characterized in that: The components include: Anti-inflammatory drugs; Nano inorganic calcium salt; Biodegradable polymers.
2. The bone repair-specific silk screen membrane according to claim 1, characterized in that: The anti-inflammatory drug is one or more combinations of nimesulide, curcumin, bleomycin, cyclophosphamide, celecoxib, doxorubicin hydrochloride, adriamycin, etoricoxib, and meloxicam.
3. The bone repair-specific silk screen membrane according to claim 1, characterized in that: The nano inorganic calcium salt is at least one of nano tricalcium phosphate, nano hydroxyapatite and nano calcium silicate.
4. The bone repair-specific silk screen membrane according to claim 1, characterized in that: The biodegradable polymer is polylactic acid.
5. The bone repair-specific silk screen membrane according to claim 1, characterized in that: The mass ratio of the nano inorganic calcium salt to the biodegradable polymer is 1:10-100.
6. A method for preparing a silk screen membrane for bone repair according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: Dissolve 10-100 parts of dry biodegradable polymer in a solvent, add 1 part of nano inorganic calcium salt, 0.5-2 parts of grafted polymer, and 0.1-0.3 parts of catalyst, and stir the mixture at 50-80° C. for 1-3 hours to obtain a spinning solution; Step 2: Spin the spinning solution obtained in step 1 in an electrospinning machine, the spinning voltage is 12-25 kV, a No. 20 needle with an inner diameter of 0.6 mm is used, the distance between the spinneret and the receiving screen is 20-25 cm, the receiving screen is a stationary flat plate covered with aluminum foil, the spinning solution flow rate is 2-3 mm / min, the spinning temperature is 20-30 ° C, and an electrospinning membrane is obtained; Step 3: Place the electrospun membrane in 60% ethanol, clean it with an ultrasonic cleaner for 10 minutes, take it out and rinse it with deionized water, and dry it in an oven at 30-40°C for later use; Step 4: Place the electrospun membrane cleaned and dried in step 3 between the two plates of a normal pressure plasma treatment device, and perform plasma treatment for 90 to 180 seconds in an argon atmosphere at a discharge voltage of 200V; Step 5: prepare the anti-inflammatory drug into a saturated solution, immerse the electrospun membrane treated by plasma in step 4 in the saturated solution of the anti-inflammatory drug for 30 minutes, take it out and dry it to obtain a silk screen membrane for bone repair.
7. The method for preparing a special silk screen membrane for bone repair according to claim 6, characterized in that: The solvent in step 1 is a mixture of any two of dichloromethane, chloroform and N,N-dimethylformamide.
8. The method for preparing a special silk screen membrane for bone repair according to claim 6, characterized in that: The grafted polymer in step 1 is any one of chitosan, dextran and dopamine.
9. The method for preparing a special silk screen membrane for bone repair according to claim 6, characterized in that: The catalyst in step 1 is any one of stannous chloride and stannous lactate.
10. The bone repair-specific silk screen membrane according to claim 1, characterized in that: Its components may also include: potassium citrate and sodium bicarbonate.
Citation Information
Patent Citations
Method for preparing nano-fiber-based guided bone regeneration membrane
CN103611197A
A method for preparing a multifunctional electrospun fiber dressing
CN109943976B